New method for file deduplication in cloud storage - Chao YANG; Qian JI; Si-chun XIONG; Mao-zhen LIU; Jian-feng MA; Qi JIANG; Lin BAI (Tongxin xuebao)
Deduplication is widely used in cloud storage service to save bandwidth and storage resources,however,the security of client deduplication still flaws in an external attack to access a user’s private data.Xu-CDE,a deduplication solution of encrypting data for multi-client was first proposed,which could protect the privacy of data from the external attackers and honest but curious server,with favorable theoretical meaning and representativeness.However,in Xu-CDE,the user ownership authentication credentials were lack of instantaneity protection,which could not resist replay attack.As an improvement to the flaw,the protocol MRN-CDE (MLE based and random number modified client-side deduplication of encrypted data in cloud storage) was proposed,adding random number in order to ensure the instantaneity of the authentication credentials,and using the algorithm of MLE-KPto extract key from original file to replace the file itself as an encryption key.As a consequence,the new protocol improved security while significantly reduced the amount of computation.After the safety analysis and the actual tests,results show that based on Xu-CDE,the proposed protocol MRN-CDE has stronger security of ownership,and improves time efficiency.Specially,the new protocol works better on large files in cloud with a certain value.